2020
DOI: 10.12659/msm.926766
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomics Analysis Identifies Abnormal Energy, Lipid, and Amino Acid Metabolism in Abdominal Aortic Aneurysms

Abstract: Background Abdominal aortic aneurysm (AAA) is a complicated aortic dilatation disease. Metabolomics is an emerging system biology method. This aim of this study was to identify abnormal metabolites and metabolic pathways associated with AAA and to discover potential biomarkers that could affect the size of AAAs. Material/Methods An untargeted metabolomic method was used to analyze the plasma metabolic profiles of 39 patients with AAAs and 30 controls. Multivariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Many studies have shown that stress response or disease can affect amino acid metabolism, energy metabolism, and lipid metabolism [ 45 , 46 , 47 ]. Amino acids such as glutamate, aspartate, phenylalanine, tyrosine, and leucine are pivotal metabolic intermediates in the central carbon metabolic pathway, including TCA cycle and pentose phosphate pathway [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that stress response or disease can affect amino acid metabolism, energy metabolism, and lipid metabolism [ 45 , 46 , 47 ]. Amino acids such as glutamate, aspartate, phenylalanine, tyrosine, and leucine are pivotal metabolic intermediates in the central carbon metabolic pathway, including TCA cycle and pentose phosphate pathway [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that altered lipid metabolism contributes to the formation of atherosclerotic plaques and the weakening of the aortic wall, leading to the development of AS ( Zhu et al, 2016 ; Guo et al, 2019 ). The induction of AAA through experimentation leads to a significant change in the metabolic profile of both the aortas and blood, primarily focusing on the modification of lipid metabolism ( Guo et al, 2020 ; Chao de la Barca et al, 2022 ). In addition, SIRT4 in mitochondria regulates fatty acid oxidation and its deficiency promotes AS through NF-κB pathway activation ( Chang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental induction of AAA leads to significant changes in the metabolic composition of both aortas and blood. These changes are primarily focused on the disruption of nitric oxide production, lipid metabolism, and energy-related metabolic pathways ( Guo et al, 2020 ; Chao de la Barca et al, 2022 ). Elevated lipoprotein levels have been found to be an independent indicator of increased risk of disease in patients with AAA ( Kubota et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…L-proline is a component of collagen metabolites and increased L-proline level may be related to the activation of collagen breakdown (Y. Guo et al, 2020 ). In addition, glycine was reported to play a role in affecting platelet membrane potential and hence aggregation capacity ( Schemmer et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%